3D printing of heterogeneous microfibers with multi‐hollow structure via microfluidic spinning. (8th July 2022) - Li, Wei; Yao, Kun; Tian, Lingling; Xue, Chang; Zhang, Xu; Gao, Xinghua
Abstract: Tissues with tubular structures play important roles in the human bodies, such as mass transport, nutrition exchange, and waste filtration. However, it remains a challenge to generate micro‐scaffolds with well‐defined luminal structure in biomedical field. In this study, we proposed a novel method to fabricate multi‐component microfibers with multi‐hollow structure via microfluidic spinning, which can subsequently be integrated with 3D printing for tissue‐like block assembling. To achieve this goal, we fabricated a microchip using a 3D printed template with adjustable heights. Utilizing this microchip, we successfully generated the Calcium alginate microfibers with multi‐components and defined hollow structures in a controllable manner. Then this microfluidic spinning method was integrated with a 3D mobile platform to assemble the microfibers into a grid‐like 3D architecture. The resulted 3D scaffolds exhibited good organization and maintained the hollow structure of the fibers. Furthermore, we successfully developed a bronchus model utilizing this strategy by loading pulmonary bronchial epithelium cells and endothelial cells into microfibers with two hollow structures. The present strategy provides a potential platform to rebuild the lumen‐like tissues using microfibers.